Rancang Bangun Modul Percobaan Gerbang Logika Dan Flip-Flop Di Labolatorium Elektronika Dan Digital Fakultas Teknik Elektro Universitas Mataram - Pramesty, Kinkin Ayu Pramesty; Darmawan, Budi; Ch, Syafaruddin (Depertment of Electrical Engineering University of Mataram, 2024)
This research aims to deepen understanding of theory in lectures through practicum. The practicum module was created to facilitate data retrieval during a practicum at the Electronics and Digital Laboratory, Faculty of Electrical Engineering, University of Mataram, which was realized in the design of the logic gate and flip-flop experiment module, based on the logic gate and flip-flop experiment module, on logic gates using 7 IC namely AND gate (IC 7408), OR gate IC (IC 7432), NOT gate IC (IC 7404), NAND gate IC (IC 7400), NOR gate IC (IC 7402), XOR gate IC (IC 7486), XNOR gate IC (IC 74266), resistors, led indicators, and switches, on Flip-Flops using 2 logic gate ICs namely NOT gate IC (IC 7404), NAND gate IC (IC 7400), and a JK Flip- Flops (IC 7476), and clocks that use push buttons that have been connected to Arduino, resistors, led indicators, and switches, from the designed modules, the results show that the logic gates and flip-flop experiments are by the experimental steps and the truth table his.